Improving Student's Writing Skills Through the Application of Content Structure Strategy - Hamdan Hamdan; Syaprizal Syaprizal (EDULIA: English Education, Linguistic and Art Journal, 2020)
The purpose of this study was to determine the effect of content structure strategy on improving student's writing skills and to determine whether or not the content structure strategy was effective in increasing student's writing skills. This study used a cluster random sampling method consisting of 28 students taken as the research sample from three classes. The results showed that there was a significant difference between student scores before and after treatment. Student writing recount text increases after use. In addition, the calculated t-test match result is higher than the matched t-test result table coefficient. In conclusion, there was a significant different between the student's achievement before and after the treatment. The student's mean score on the post-test was higher than the mean score on the pre-test. This shows that the content structure strategy is effectively used in learning recount text in Al-Ikhlas Lubuklinggau Junior High School. Keywords: Ability, Content Structure, Strategy, Writing